Screening for lignin peroxidase genes in natural isolates of white rot fungi - V. Cifuentes; C. Martinez; G. Pincheira (Fungal Genetics Reports, 1992)
To find lingin peroxidase genes similar to those of Phanerochaete chrysosporium, we have studied several species of white rot fungi collected in nature. The methodology has been DNA hybridization techniques using two synthetic oligonucleotides with a sequence that corresponds to a fragment of the H8 lignin peroxidase gene from P. chrysosporium (Schalch et al. 1989. Mol. Cell. Biol. 9:2743-2747) controlling the structure of the predominant form of the enzyme in this fungus.